The Variational Methods for Solving Random Models (International Journal of Innovative Research in Computer Science & Technology, 2024)
This paper studies the solutions of variational  methods for random ordinary (partial) dierential equations in  L2−space. These methods are called Galerkin method,  Petrov-Galerkin method, Least-Squares method and Collocation  method. Some basic properties of these methods where applying  on random problems will be shown throughout some numerical  examples.  Random models
Keywords: Random models; Second order random variable